Membangun Kesadaran Pentingnya Strategi Manajemen Diri Dalam Mengatasi Beban Kerja Mental Pada Mahasiswa Pekerja Prodi Manajemen Universitas Muhammadiyah Gresik - Hidayati, Roziana Ainul; Basyari, Alif Sulthon (Jurnal Pengabdian Manajemen, 2024)
Mental workload as the difference between the workload demands of a task and capacity. Mental workload is a human evaluation or assessment of the limits of attention load during optimal task performance, which is influenced by the workload demands of a task and the worker's capacity in handling the task. Various risks of studying while working can occur, such as fatigue due to too much studying and working, lack of time to relax and socialize, lack of time for needed sleep, and others. The indicator that has the most dominant influence on the mental workload of working students at the Faculty of Economics, University of Muhammadiyah Gresik is the Time Needs Indicator (Temporal Demand/TD). The impact of the high mental workload experienced by working students often causes them to experience fatigue and lack of focus in attending lectures. In addition, the increase in lecture assignments also results in an increase in their burden or responsibility so that it more or less interferes with performance achievement. Therefore, the purpose of this study is so that the object can be more aware of the importance of self-management strategies for mental processing. The expected impact is so that the results of this activity can be used as a reference for compiling self-management strategies.